A Multicenter, International Cohort Analysis of 1435 Cases to Support Clinical Trial Design in Acute Pancreatitis - Farkas, Nelli; Hanák, Lilla; Mikó, Alexandra; Bajor, Judit; Sarlós, Patrícia; Czimmer, József; Vincze, Áron; Gódi, Szilárd; Pécsi, Dániel; Varjú, Péter; Márta, Katalin; Hegyi, Péter Jenő; et al. (Frontiers in Physiology, 2019)
Background C-reactive protein level (CRP) and white blood cell count (WBC) have been variably used in clinical trials on acute pancreatitis (AP). We assessed their potential role. Methods First, we investigated studies which have used CRP or WBC, to describe their current role in trials on AP. Second, we extracted the data of 1435 episodes of AP from our registry. CRP and WBC on admission, within 24 hours from the onset of pain and their highest values were analyzed. Descriptive statistical tools as Kruskal-Wallis, Mann-Whitney U, Levene’s F tests, Receiver Operating Characteristic (ROC) curve analysis and AUC (Area Under the Curve) with 95% confidence interval (CI) were performed. Results Our literature review showed extreme variability of CRP used as an inclusion criterion or as a primary outcome or both in past and current trials on AP. WBC is rarely used as an inclusion criterion and never as a primary outcome. In our cohort, CRP levels on admission poorly predicted mortality and severe cases of AP; AUC:0.669 (CI:0.569-0.770); AUC:0.681 (CI:0.601-0.761), respectively. CRP levels measured within 24 hours from the onset of pain failed to predict mortality or severity; AUC:0.741 (CI:0.627-0.854); AUC:0.690 (CI:0.586-0.793), respectively. The highest CRP during hospitalization had equally poor predictive accuracy for mortality and severity AUC:0.656 (CI:0.544-0.768); AUC:0.705 (CI:0.640-0.769) respectively. CRP within 24 hours from the onset of pain used as an inclusion criterion markedly increased the combined event rate of mortality and severe AP (13% for CRP>25mg/l and 28% for CRP>200mg/l). WBC count, both on admission and within 24 hours from the onset of pain, proved to be a poor predictor of mortality and severity of AP AUC: 0.648 (CI: 0.546-0750) AUC: 0.630 (CI: 0.563-0.696) respectively. In addition, its elevation as an inclusion criterion also failed to increase the event rate of mortality and severity. Conclusion CRP within 24 hours from the onset of pain as an inclusion criterion elevates event rates and reduces the number of patients required in trials on AP. d in trials on AP.